The climatic rhythm and blooms of cyanobacteria in a tropical reservoir in São Paulo, Brazil - Ogashawara, I.; Zavattini, João Afonso [UNESP]; Tundisi, J. G. (Instituto Internacional de Ecologia, 2014)
The present study sought to develop a methodology to analyse water quality based on the concepts and methods of climate and climatology. Accordingly, we attempted to relate hydro- and limnometeorological techniques and methodologies to a rhythmic analysis technique developed within the context of the Brazilian geographical climatology. Our goal was to assess and analyse cyanobacterial blooms, the main index of water quality for the reservoirs of the “Alto Tietê” Basin and, consequently, the Metropolitan Region of São Paulo, an area of high environmental complexity due to its high degree of development and high population density. The meteorological data used were collected by the Institute of Astronomy, Geophysics and Atmospheric Sciences at the University of São Paulo meteorological station, and the limnological data were collected through the Hydrological Monitoring System implemented by SABESP in the Billings and Guarapiranga Reservoirs and the laboratory of the same entity. The rhythmic and integrated analysis showed that the process of cyanobacterial blooms is dependent on a combination of meteorological factors as temperature and wind intensity that may disrupt the stability of the reservoir, providing the conditions necessary for the development of cyanobacteria during the stabilisation process. The pace of the Atlantic Polar Front Entrance during the winter in São Paulo is a limiting factor for the growth of cyanobacteria because of their high frequency, thus maintaining the balance of the reservoir throughout this period. The weather types those could cause a instability in the water column were: Cold Front entrance (66.67%), conflict between masses (22.22%) and the Tropical Instability Line (11.11%). The possibility for prevention and forecasting periods advise when these reservoirs should not be used, mainly with regard to recreational activities.

O presente trabalho buscou desenvolver uma metodologia para análise da qualidade da água com base em conceitos e métodos do clima e da climatologia respectivamente. Dessa forma, buscou-se relacionar técnicas e metodologias hidrometeorológicas e limno-meteorológicas com a técnica de análise rítmica desenvolvida dentro da climatologia geográfica brasileira para avaliar e analisar as florações de cianobactérias, principal índice de qualidade de água encontrado nos reservatórios da Bacia do Alto Tietê e consequentemente da Região Metropolitana de São Paulo, área de alta complexidade ambiental devido ao seu alto grau de desenvolvimento e a sua alta densidade populacional. Os dados meteorológicos utilizados para o desenvolvimento do trabalho foram coletados a partir da estação meteorológica do Instituto de Astronomia, Geofísica e Ciências Atmosféricas da Universidade de São Paulo e os dados limnológicos foram coletados por meio do Sistema de Monitoramento Hidrológico implantado pela SABESP nos reservatórios de Billings e Guarapiranga assim como os dados laboratoriais da mesma entidade. A análise rítmica e integrada de todos os dados mostrou que o processo de floração de cianobactérias é dependente não apenas de um fator específico, mas de uma combinação de fatores meteorológicos como temperatura e intensidade do vento que podem quebrar a estabilidade do reservatório e proporcionar durante a estabilização as condições necessárias para o desenvolvimento das cianobactérias. Também foi mostrado como o ritmo de entrada de Frentes Polares Atlânticas, durante o inverno paulistano, é um fator que limita o crescimento das cianobactérias devido à sua alta frequência, mantendo o reservatório desequilibrado por todo o período. Os tipos de tempo que podem causar instabilidade na coluna da água foram identificados com: entrada de Frentes Frias (66,67%), conflitos entre massas (22,22%) e Linha de Instabilidade (11,11%). Mostra-se assim a importância do trabalho para a prevenção e previsão de períodos inapropriados para o uso desses reservatórios principalmente para atividade de recreação.
O ritmo climático e as florações de cianobactérias em um reservatório tropical em São Paulo, Brasil
Keywords: Geographical climatology; Rhythmic analysis; Stratification; Mixing; Cyanobacteria; Climatologia geográfica; Análise rítmica; Estratificação; Mixing; Cianobactérias